Complementary pre‐screening strategies to uncover hidden prodromal and mild Alzheimer's disease: Results from the MOPEAD project. Issue 6 (26th July 2021) - Boada, Mercè; Rodrigo, Adrián; Jessen, Frank; Wimblad, Bengt; Kramberger, Milica G.; Visser, Pieter Jelle; Simó, Rafael; Rodríguez‐Gomez, Octavio; Ciudin, Andreea; Georges, Jean; Dumas, Annete; Maguire, Peggy; et al.
Abstract: Introduction: The Models of Patient Engagement for Alzheimer's Disease (MOPEAD) project was conceived to explore innovative complementary strategies to uncover hidden prodromal and mild Alzheimer's disease (AD) dementia cases and to raise awareness both in the general public and among health professionals about the importance of early diagnosis. Methods: Four different strategies or RUNs were used: (a) a web‐based (WB) prescreening tool, (2) an open house initiative (OHI), (3) a primary care–based protocol for early detection of cognitive decline (PC), and (4) a tertiary care–based pre‐screening at diabetologist clinics (DC). Results: A total of 1129 patients at high risk of having prodromal AD or dementia were identified of 2847 pre‐screened individuals (39.7%). The corresponding proportion for the different initiatives were 36.8% (WB), 35.6% (OHI), 44.4% (PC), and 58.3% (DC). Conclusion: These four complementary pre‐screening strategies were useful for identifying individuals at high risk of having prodromal or mild AD.